Association of Serum Zinc Level with Severe Pneumonia in Children - Pushpa; Lohano, Mohan; Memon, Mumtaz (Pakistan Journal of Nutrition, 2009)
Pneumonia is the leading cause of childhood mortality especially in developing countries affecting approximately 151 million cases each year. Malnutrition especially deficiency of micronutrients such as zinc, has shown to increased incidence and severity of pneumonia. In developing countries zinc deficiency is common in children due to lack of intake of animal foods and high dietary phytates (myoinositol hexaphosphate) content. This study was designed to document the association of serum zinc level with severe pneumonia in children of 2-60 months age. A case-control study was conducted in the department of physiology, Liaquat University of Medical and Health Sciences, Jamshoro and cases were collected from outpatient department of pediatrics, Liaquat Medical College and Hospital Jamshoro, Sindh-Pakistan. Fifty cases of severe pneumonia and fifty cases of control group of same age, sex and nutritional status were recruited for the study. Mean ±SD serum zinc level of group I was 184.92 ±44.11 μg/dl and it was 206.76 ±47.59 μg /dl for group II, which was highly significant statistically (p = 0.019).